Activity Screening and Structure Modification of Trigonelline as New Anticancer Drug for Non Small Cell Lung Cancer Through In Silico - Kelvin F. Pratama; Muhammad Fauzi; Aliya Nur Hasanah (Indonesian Journal of Pharmaceutical Science and Technology, 2020)
The biggest case of death in 2018 is caused by lung cancer. Non-small cell lung cancer (NSCLC) is most common. One of the cause lung cancer is the over expression of EGFR. Erlotinib is the first line of anticancer for NSCLC with EGFR mutations. However, erlotinib can cause side effects such as liver damage therefore new safe anticancer is needed. Trigonelline is an alkaloid compound from coffee beans that had anticancer activity in pancreatic cancer cells by inhibiting Nrf2 in vitro and in vivo at concentrations of 0.1-1 µM. Development of cancer cells by Nrf2 is regulated by EGFR. In this study screening and modification of trigonelline structure was carried out to obtain compounds that have anticancer activity on NSCLC against EGFR computationally. The research procedures carried out are modification of ten trigonelline derived structures, the molecular docking and prediction of physicochemical profiles from trigonelline and its modification also their ADMET. Based on results, KF9 has the lowest free energy of binding which was -8,88 kcal/mol and binds to Met769 which has biological activity with receptor. KF9 has good physiochemical profile and absorption, distribution, also toxicity parameters. KF9 has potential to become a new anticancer drug for NSCLC.Keywords: Coffee, Drug discovery and Drug development, Molecular structure modification, Nonsmall cell lung cancer, Trigonelline